Development of a test protocol to identify potential risk factors for lower limb injuries in ballet dancers - Madsen, S. B.; Lake, M.; de Zee, M. (ISBS Proceedings Archive (Michigan), 2020)
The aim of the present study was to develop a test protocol to identify potential risk factors for lower limb injuries during ballet jump landings. Two ballet dancers, a beginner level and an advanced level dancer, participated in the study. The dancers performed multiple Sautés in first position, Grand Jeté, and Grand Pas de Chat jump landings on a plantar pressure mat on top of a force platform. The participants wore ballet slipper thongs, while a three-segment kinematic model of the foot was used to provide a more detailed understanding of foot posture during landings, and to investigate how the dancers adapted to the high foot/ankle loadings. Potential risk factors were identified as high free moment peaks, high impact velocities, and improper technique with missing turnouts during landings. Furthermore, there seems a potential to distinguish between dancers` ability levels and associated injury risks.